Summer term - Cox, Pamela (London : Hodder childern book, 2019)
There's a mystery at the nearby stables - someone has stolen money and then poor Julie's horse. Can the third form help old girls Bill and Clarissa discover who is behind it?
Keywords: English - Teenager Fiction Book